2018
DOI: 10.3390/md16120507
|View full text |Cite
|
Sign up to set email alerts
|

Alanine-Scanning Mutagenesis of α-Conotoxin GI Reveals the Residues Crucial for Activity at the Muscle Acetylcholine Receptor

Abstract: Recently, the muscle-type nicotinic acetylcholine receptors (nAChRs) have been pursued as a potential target of several diseases, including myogenic disorders, muscle dystrophies and myasthenia gravis, etc. α-conotoxin GI isolated from Conus geographus selectively and potently inhibited the muscle-type nAChRs which can be developed as a tool to study them. Herein, alanine scanning mutagenesis was used to reveal the structure–activity relationship (SAR) between GI and mouse α1β1δε nAChRs. The Pro5, Gly8, Arg9, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…However, the significant decrease in Koff values suggests stronger interaction of the cyclic analogues within one, or both, of the two orthosteric muscle nAChR binding sites. Considering the high sequence homology of α-CIA with α-MI and α-GI, α-CIA is most likely binding at the α-δ interface 35,36 . It has been demonstrated that the ACh binding pocket is mostly composed of hydrophobic residues that interact with residues of the two conotoxin loops formed by the disulfide bridges.…”
Section: Discussionmentioning
confidence: 99%
“…However, the significant decrease in Koff values suggests stronger interaction of the cyclic analogues within one, or both, of the two orthosteric muscle nAChR binding sites. Considering the high sequence homology of α-CIA with α-MI and α-GI, α-CIA is most likely binding at the α-δ interface 35,36 . It has been demonstrated that the ACh binding pocket is mostly composed of hydrophobic residues that interact with residues of the two conotoxin loops formed by the disulfide bridges.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the small size and angle of Gly at position 9 is determining for the high affinity [19,23]. More recently, it was shown for toxin GI that the substitution of a Gly for an Ala reduced the affinity for the α/δ binding site by approximately 30-fold [24]. It has been suggested that the Gly has a significant impact on the right-handed helical turn from the α-helix.…”
Section: Discussionmentioning
confidence: 99%
“…Alanine scanning mutagenesis is another experimental technique that has been computerized to accelerate ‘hotspot’ prediction, mostly at protein-protein interface. This method involved the site-directed mutagenesis of specific residues to alanine to assess the contribution of the amino acid towards protein stability and function [ 103 , 104 , 105 ]. Computational alanine scanning (CAS), a robust alternative to its experimental counterpart, permits the rapid scanning of protein surface for amino acid clusters vital for protein-protein association [ 74 ].…”
Section: Computational Methods For the Prediction Of Protein-protementioning
confidence: 99%